The Pin: An Orthopaedic Transformation: Current Concept Review - Lindsay, Sarah E.; Holmes, Stephanie; Owen, Jonas; Swarup, Ishaan; Halsey, Matthew (Journal of the Pediatric Orthopaedic Society of North America, 2022)
The stainless-steel pin has become an important part of operative orthopaedics over the last several decades. It is used in all subspecialties as tool to localize a lesion or to effectuate reduction, as a conduit for implant placement (screw or blade plate), as a guide for making an osteotomy, and as an implant that can stabilize bone whether it is placed in an open or percutaneous manner. While simple and ubiquitous to the craft of orthopaedics, it has revolutionized the care of children with orthopaedic conditions. This review highlights the history and the applications of the simple pin that can assist in obtaining good results in common problems.